Stairs leading to the mandapa - Temples of India Project Team (Jio Institute, 2024)
A closer look at the stairs, leading to the mandapa, shows that the bottom stair, although lacking carvings, is made like the chandrashila (moon stone) found in ancient temples. The top two stairs were decorated with the original broken parts of the temple at the time of renovation. The pillars which are placed on both sides of the steps are similar to the pillars at the entrance of the temple complex.